An fMRI Study of the Effects of Food Familiarity and Labeling on Brain Activation. Issue 4 (1st October 2016) - Wolfe, Kara; Jo, WooMi; Olds, David; Asperin, Amelia; DeSanto, Jeffrey; Liu, Wen-Ching
ABSTRACT: Consumers' food preferences and choices with a wider range of options have become more complex and are influenced by various factors. The evolution of neuroimaging in consumer sciences enables scholars to conduct more scientific-based research in investigating people's food choices. The purpose of this pilot study was to investigate whether or not there were differences in brain activity for familiar and unfamiliar foods which could lead to a better understanding of consumers' reaction to food. This study used functional magnetic resonance imaging (fMRI) to examine brain activity among nine healthy male participants while viewing pictures of food. All rounds of food pictures had activation in the cingulate gyrus and occipital areas of the brain; however, there were some significant differences in activation by the types of foods viewed. The unfamiliar foods showed significant activation in the parietal lobe areas and the insula, while the unfamiliar foods with labels had more activation in the prefrontal areas of the brain. The implications from the results are that brain activation while viewing food images is related to reward and inhibition.